2020
DOI: 10.1080/03043797.2019.1701632
|View full text |Cite
|
Sign up to set email alerts
|

Initiatives, experiences and best practices for teaching social and ecological responsibility in ethics education for science and engineering students

Abstract: Zandvoort (2021) Initiatives, experiences and best practices for teaching social and ecological responsibility in ethics education for science and engineering students,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…It is suggested that "a quantum awareness or concepts course" on the undergraduate level, if possible in the first year, "to introduce students to the field early" would be beneficial [83] (p. 18), and that new courses are already being developed [84]. At the same time, it is recognized that the teaching of technical students on the 'social' aspects of technologies is lacking [85][86][87][88][89][90]. Techno-determinism and techno-optimism are recognized as biased forms of reporting within the STEM education literature [91][92][93][94], as is evident as well within statements such as "the need for quantum workforce and a well-educated society with knowledge and attitudes towards the acceptance of QT is imminent" [95] (p. 1).…”
Section: Education and Quantum Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that "a quantum awareness or concepts course" on the undergraduate level, if possible in the first year, "to introduce students to the field early" would be beneficial [83] (p. 18), and that new courses are already being developed [84]. At the same time, it is recognized that the teaching of technical students on the 'social' aspects of technologies is lacking [85][86][87][88][89][90]. Techno-determinism and techno-optimism are recognized as biased forms of reporting within the STEM education literature [91][92][93][94], as is evident as well within statements such as "the need for quantum workforce and a well-educated society with knowledge and attitudes towards the acceptance of QT is imminent" [95] (p. 1).…”
Section: Education and Quantum Technologiesmentioning
confidence: 99%
“…Indeed, given that students have different interests [96], adding the 'social' might broaden the interest into quantum. The mapping exercises might counter the recognized problem that the teaching of technical students in 'social' aspects is lacking [85][86][87][88][89][90] and that techno-determinism and techno-optimism are recognized as biased forms of reporting within the STEM education literature [91][92][93][94], which also seems to be evident in quantum policy views on education, as evident from statements such as "the need for quantum workforce and a well-educated society with knowledge and attitudes towards the acceptance of QT is imminent" [95] (p. 1). It is suggested that "a quantum awareness or concepts course" on the undergraduate level, if possible in the first year "to introduce students to the field early" would be beneficial [83] (p. 18).…”
Section: Quantum Technologies and Educationmentioning
confidence: 99%
“…2.1.2. Goals oriented towards stakeholders Another goal is raising awareness of the perspectives of different stakeholders (Haws 2001;Beever & Hess, 2016;Dempsey, Stamets, and Eggleson 2017;Bowe 2018, 2019;Børsen et al 2021;Herkert, Borenstein, and Miller 2020). According to Haws (2001, 227), case instruction needs to facilitate students' understanding of engineering outcomes from the perspective of the larger community.…”
Section: Goals Of Engineering Ethics Case Studiesmentioning
confidence: 99%
“…Yet information about how to teach ethics is seldom a part of instructor training, even though the inclusion of socio-environmental factors into science education has been shown to increase students' motivation for and enjoyment of their studies (Herreid, et al, 2012;McKim, 2010;Steele, 2016). Education in STEM disciplines is needed for discipline-specific ethics (Børsen et al 2020;van den Hoven, 2016), and case studies have long been employed for that purpose (Barden et al, 1997). Practitioners justify teaching ethics through case studies with a range of different rationales, including that 'there are ethical land mines everywhere' and 'many scientists act or speak as if they bear no responsibility for the use of their discoveries-as if their job is to uncover the secrets of the universe irrespective of the consequences' (Herreid et al, 2012, p. 268).…”
Section: Introductionmentioning
confidence: 99%